Effect of twin‐to‐twin delivery interval on umbilical cord blood gas in the second twins - Tak‐Yeung Leung; Wing Hung Tam; Tse‐Ngong Leung; Ingrid Hung Lok; Tze Kin Lau (2002)
Objective To examine the effect of twin‐to‐twin delivery interval on the umbilical cord blood gas status of the second twin following vaginal delivery. Design A retrospective study. Setting The department of obstetrics and gynaecology in a university teaching hospital. Population Twin deliveries at or beyond 34 weeks of gestation over a period of five years, with the first twin delivered vaginally. Twins with any antepartum complications including discordant growth, intrauterine growth restriction, intrauterine death, fetal malformations and pre‐eclampsia were excluded. Methods The correlation between the twin‐to‐twin delivery interval, and both the umbilical arterial and venous blood gas parameters of the second twin, including pH, partial pressure of CO 2 and base excess, were studied. Results A total of 118 cases were reviewed. The mean gestation at delivery was 37.1 weeks. The median twin‐to‐twin delivery interval was 16.5 minutes. There were significant negative correlations between twin‐to‐twin delivery interval and both the umbilical cord arterial and venous pH and base excess of the second twin ( P <0.05 ). There were also significant positive correlations between both arterial and venous partial pressure of CO 2 and the delivery interval ( P <0.05 ). Similar changes were found even if the analyses were limited to those who had normal vaginal deliveries. The umbilical arterial pH of Twin 2 was <7.00 in none of the cases delivered within 15 minutes of the birth of Twin 1, 5.9% if within 16–30 minutes, and 27% if more than 30 minutes. Among those with an inter‐twin delivery interval of more than 30 minutes, 73% had cardiotocographic evidence of fetal distress which required operative delivery. Conclusions Umbilical cord arterial and venous values of pH, partial pressure of CO 2 and base excess of the second twin deteriorate with increasing twin‐to‐twin delivery interval. Risks of fetal distress and acidosis in the second twin are high when the twin‐to‐twin delivery interval is beyond 30 minutes.